Colonialism and revolution in the Middle East : social and cultural origins of Egypt's 'Urabi movement - Cole, Juan Ricardo (Princeton studies on the Near East., 1993)
In this book Juan R.I. Cole challenges traditional elite-centered conceptions of the conflict that led to the British occupation of Egypt in September 1882. For a year before the British intervened, Egypt's viceregal government and the country's influential European community had been locked in a struggle with the nationalist supporters of General Ahmad al-'Urabi. Although most Western observers still see the 'Urabi movement as a "revolt" of junior military officers